Pengaruh Produksi Dan Konsumsi Terhadap Impor Komoditi Beras Di Provinsi Jambi - Heppi Syofya (Universitas Batanghari Jambi, 2018)
Rice is a strategic commodity as food for the people of Indonesia, so that the production, supply, procurement and distribution of rice becomes very important in the framework of food security, increasing income and welfare of farmers, in order to stabilize the interest of public consumption in general, import of rice is not always indicated because the inability of the region to produce rice but it is necessary to maintain the availability of rice in order to avoid a deficit that will affect the price increase, given the function of rice as staple food, rice sales will be continuous, meaning that sales will continue throughout the year so that the business prospect is considered sufficient promising for years to come. In farm processing, farmers seek to obtain economically profitable, where the cost incurred can produce maximum production. To support the availability of rice food, the procurement of rice’s, especially from regional sources. The procurement of rice in Jambi province, in addition to the procurement of rice in the region, also comes from the national move and rice stock from the previous year. Keyword’s : primer sectors, rice commodity